Improvement of engine bracket design by using topology optimization and additive manufacturing - Said, Zaitul Akma (2018)
Engine bracket plays a crucial part especially in aerospace industry where the mass of bracket affected the performance of aircraft. However, reduction in mass might affected the performance of the bracket. Topology optimization (TO) is a process of optimizing the material by a given design space in response to the set of loads, boundary conditions and constraints in order to maximize the performance. TO result produces complex geometry while additive manufacturing (AM) is a technology to manufacture complex model. The purpose of this study is to obtain a fully optimized lightweight of engine bracket design with capability to withstand the load of the engine by using topology optimization technique.In addition, the effect of manufacturability when incorporating topology optimization in additive manufacturing would also be investigated. In order to minimize the mass and maintaining the stiffness of the bracket, topology optimization by SolidThinking Inspire has been applied on two different design spaces which were named by Topology Optimization I (TO I) and Topology Optimization II (TO II). A baseline of target specification on AM outputs which are printing time, raw material mass and support material mass has been obtained by using CreatWare V6.4.3 from a total of 300 existing topology optimized designs of engine bracket from GrabCAD. Remodelling on topology optimized design was done by CATIA V5R20 based on TO and AM constraints in order to fit in the target specification baseline. AM was applied in order to demonstrate the manufacturability for topology optimized design by using Fused Depostion Modelling (FDM) 3D printer with ABS material. In addition, the modification on unsmoothed geometry produced by TO was developed in order to make the design feasible to be manufactured. The result of the study showed the mass of the optimized design was 52% less compared to original design without sacrificing the performance since the von Mises stress of the optimized design was slightly different compare to original design. Based on the study, fabrication of topology optimized design using AM was considered successful but support material was still required for complex geometry produced by TO.